Analisis dan Perancangan Sistem Informasi Monitoring Call Visit (Studi Kasus PT. ABC) - Muhammad Iduan Martin; Bondan Sapta Prakoso; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
PT. ABC is a pharmaceutical company engaged in gastroenterology, urology and oncology. This company relies on the sales force to increase product sales through visits or call visits to various hospitals in Indonesia. To improve sales force performance, sales managers want to increase SFE (Sales Force Effectiveness). SFE is a framework that aims to increase the level of effectiveness of the sales force by monitoring and directing sales force sales activities, one of which is with the help of an information system. Therefore, an information system is needed to make it easier for managers to monitor sales force activities in conducting call visits. The purpose of this study is to document the results of the analysis and design and evaluate the results of the analysis and design. This study uses an OOAD (Object-Oriented Analysis and Design) approach, which is, analyzing and designing a system based on the objects involved. The design is done by describing the Unified Modeling Language notation. The results of the analysis and design will be evaluated using the traceability matrix and cognitive walkthrough methods. The evaluation of the traceability matrix aims to define requirements and designs that are made to be traceable. From the results of the traceability matrix, it can be concluded that all requirements have been sequenced and can be traced. The cognitive walkthrough evaluation aims to determine the learnability of a product by running a product prototype. From the results of the cognitive walkthrough, it can be concluded that the interface has been accepted and is easy to learn.